ช่องไม่ประสงค์จะลงคะแนนในบัตรเลือกตั้ง : ศึกษาเจตนาผู้ร่างกฎหมายกับพฤติกรรมการใช้สิทธิของผู้เลือกตั้ง - ดำรงค์ศักดิ์ ยอดทองดี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This study aims to explore the intention of the law on having a no-vote choice in the ballot to elect members of the House of Representatives and the social and economic factors influencing the exercise of the no-vote choice. This study involves documentary research, both academic and governmental, and interviews of related persons. The findings show that the intention was to guard against and correct forms of election cheating and errors caused by legal flaws, election process, intentded malpractice. It was also meant to be a mechanism to promote political participation in order to achieve higher measure of democracy. It had nothing to do with the caluse in the current (1997) constitution which stipulates voting as a duty. The study then shows that social and economic characteristics existing in constituencies tend to determine the percentage of voter exercising the no-vote choice. The constituencies with higher levels of economics and social factors tend to have higher percentages of no-vote voters. In contrast, those with lower levels of social and economic factors have lower percentages of no-vote voters. Nonetheless, in some constituencies that electoral behaviors do not fit the described pattern, this is, perhaps, because of shortterm forces such as fierce political competition, political mobilization campaigning, the mass media, or local academics in such constituencies. The strong message result in voter attitudes change in the brief period before the election.